Eating in the city Socio-anthropological perspectives from Africa, Latin America and Asia - soula, audrey; Yount-André, Chelsie; LEPILLER, Olivier; Bricas, Nicolas (éditions Quae, 2020)
This book explores changes in eating habits in African, Latin American and Asian cities. It reveals-through studies on city dwellers' food practices and representations-the inadequacy of an analytical approach to these changes in terms of Westernization, standardization, transition or convergence towards a widely applicable model. Surveys conducted in cities of the Global South revealed that city dwellers are inventing new forms of eating based on a multitude of local and/or exogenous sources. Abidjan garba and Ouagadougou bâbenda are novel dishes that exemplify this urban food invention trend. The authors of the chapters are humanities and social science specialists from Africa, Latin America and Asia who conduct research in these regions. They invite readers to take a closer look at urban food in the Global South-the picture that emerges is far removed from preconceived ideas regarding poverty, health and the individual responsibility of food eaters. This book should be of interest to a scientific audience of teachers and food systems professionals, as well as any readers interested in urban social and cultural dynamics and the development of sociological and anthropological theories from the Global South.